2004
DOI: 10.1091/mbc.e03-07-0482
|View full text |Cite
|
Sign up to set email alerts
|

Gene Silencing of CENP-E by Small Interfering RNA in HeLa Cells Leads to Missegregation of Chromosomes after a Mitotic Delay

Abstract: , i.e., unaligned chromosomes during mitosis. One unresolved question from previous studies is whether cells complete mitosis or sustain mitotic arrest in the presence of unaligned chromosomes. Using RNA interference and video-microscopy, we analyzed the dynamic process of mitotic progression of HeLa(H2B)-GFP cells lacking CENP-E. Our results demonstrate that these cells initiated anaphase after a delayed mitotic progression due to the presence of unaligned chromosomes. In some dividing cells, unaligned chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
108
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 33 publications
13
108
0
Order By: Relevance
“…Consistent with previous studies (Putkey et al, 2002;Weaver et al, 2003;Tanudji et al, 2004), cells depleted of CENP-E exhibit unaligned chromosomes close to spindle poles and misaligned chromosomes positioned between the metaphase plate and spindle poles at metaphase. Kinetochore pairs on misaligned sister chromatids showed no interaction or diminished interaction with spindle MTs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous studies (Putkey et al, 2002;Weaver et al, 2003;Tanudji et al, 2004), cells depleted of CENP-E exhibit unaligned chromosomes close to spindle poles and misaligned chromosomes positioned between the metaphase plate and spindle poles at metaphase. Kinetochore pairs on misaligned sister chromatids showed no interaction or diminished interaction with spindle MTs.…”
Section: Discussionsupporting
confidence: 91%
“…Kinetochore pairs on misaligned sister chromatids showed no interaction or diminished interaction with spindle MTs. Previous studies demonstrated that CENP-E binds to kinetochores and MTs and stabilizes their interaction, thereby contributing to silencing the mitotic spindle checkpoint (Putkey et al, 2002;Weaver et al, 2003;Tanudji et al, 2004). CENP-E associates with and activates the mitotic checkpoint kinase BubR1, indicating that the spindle checkpoint is sensed through CENP-E kinetochore activity (Chan et al, 1998(Chan et al, , 1999Mao et al, 2003;Weaver et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 21-nucleotide siRNA duplexes were designed and synthesized by QIA-GEN against hSMC1 (5Ј-CAC CAT CAC ACT TTA ATT CCA-3Ј), hRad21 (5Ј-CTG GGA GTA GTT CGA ATC TAT-3Ј), SA1 (5Ј-CAC GTA GAA TCA GAT GTT CTA-3Ј), SA2 (5Ј-TCG GTG GTA GAT GAT TGG ATA-3Ј), and CENP-E (5Ј-AAC ACG GAT GCT GGT GAC CTC-3Ј) (Tanudji et al, 2004). The target sequence for SUV39H1 is as described previously (Ait-Si- Ali et al, 2004).…”
Section: Small Interfering Rna (Sirna) Transfectionmentioning
confidence: 99%
“…To address whether the observed spindle abnormality is due to kinetochore dysfunction, CENP-E was depleted by siRNA ( Figure 4A). CENP-E depletion was shown to impair bipolar spindle attachment to kinetochores in human cells (Schaar et al, 1997;Tanudji et al, 2004). Furthermore, CENP-E depletion leads to spindle checkpoint activation (Schaar et al, 1997;Yao et al, 2000;McEwen et al, 2001;Tanudji et al, 2004).…”
Section: Cohesin Depletion Affects the Efficiency Of Spindle Assemblymentioning
confidence: 99%